Natural Capital Accounting as a Strategic Tool for Biodiversity Preservation in Resource-Intensive Firms - Nochh, Muhammad Yamin (Golden Ratio of Community Services and Dedication, 2026)
This study examines the role of Natural Capital Accounting (NCA) as a strategic instrument for biodiversity preservation within resource-intensive firms, a sector characterized by significant ecological dependencies and impacts. The research aims to evaluate how NCA reshapes corporate governance, supports ecological risk management, and enhances biodiversity-related decision-making processes. Employing a qualitative research design through a systematic literature study, the analysis synthesizes theoretical contributions and empirical evidence from interdisciplinary scholarship in environmental accounting, ecological economics, and sustainability management. The methodological approach includes thematic content analysis of peer-reviewed studies, institutional reports, and contemporary policy frameworks to identify patterns in NCA implementation, operational challenges, and biodiversity outcomes. The findings reveal that firms adopting NCA meaningfully integrate ecological considerations into strategic planning, risk assessment, and performance evaluation, demonstrating clearer pathways toward biodiversity stewardship. However, the study also identifies significant methodological limitations, including data gaps, valuation complexities, and organizational constraints that hinder effective application. The results underscore that NCA contributes positively to biodiversity preservation when supported by strong governance structures, robust ecological data, and institutional commitment. The study concludes that NCA has considerable potential as a transformative sustainability tool, offering theoretical insights into multi-capital accounting and practical implications for aligning corporate operations with global biodiversity objectives.